Application of the critical power concept in swimming? - Dekerle, J.; Brickley, G.; Sidney, M.; Pelayo, P. (Biomechanics and Medicine in Swimming X, 2006)
The concept of Critical Power (CP) has been extended to running, cycling, and swimming. However, applying the CP concept to cyclic activities imposes several assumptions (di Prampero, 1999) not always apparent to scientists and coaches. Their understanding would allow a better appreciation of the potential of this concept when applied as a tool for training.